Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1142/s0218625x01000884
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH, MORPHOLOGY, INTERFACIAL EFFECTS AND CATALYTIC PROPERTIES OF Au ON TiO2

Abstract: We survey recent studies and present new data on the growth, interactions, structure and chemistry of gold deposited on TiO 2(110) surfaces. The noble metal Au on TiO 2(110) is a model system for weak interaction of a metal with an oxide substrate; it is also of interest because Au on TiO 2 has unusually high activity as a catalyst for CO oxidation at room temperature. In this review, we present results on the growth of ultrathin films of Au on TiO 2(110), as well as the morphology, interface formation, epitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
147
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 91 publications
18
147
0
1
Order By: Relevance
“…It is not surprising that larger clusters formed after growth at, or annealing to, RT are found at step edges since the step edges can be considered as a collection of oxygen vacancies. The bimodal growth model differs from other models proposed to explain Au growth on TiO 2 110 [17,18]. Parker et al [18] have shown that the onset of 3D growth corresponds to a coverage of 0.086 ML on the stoichiometric TiO 2 110 surface and 0.15 ML on the thermally reduced surface.…”
mentioning
confidence: 84%
“…It is not surprising that larger clusters formed after growth at, or annealing to, RT are found at step edges since the step edges can be considered as a collection of oxygen vacancies. The bimodal growth model differs from other models proposed to explain Au growth on TiO 2 110 [17,18]. Parker et al [18] have shown that the onset of 3D growth corresponds to a coverage of 0.086 ML on the stoichiometric TiO 2 110 surface and 0.15 ML on the thermally reduced surface.…”
mentioning
confidence: 84%
“…Lai et al [15] studied the most stable surface (1 1 0) of rutile which includes five-fold coordinated Ti atoms rows and two-fold coordinated bridging O atoms. It was found out that nucleation of metal nanoclusters initiated at surface defects, which is thermodynamically favorable due to the high adsorption energy and Ti cation sites between bridging oxygen rows [16]. On the other hand, the most stable surface of anatase is reported by Vittadini et al [17], as (1 0 1) which serves five-fold coordinated O anions and five-fold coordinated Ti atoms as mostly preferential nucleation sites of noble metal clusters.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…The equilibrium shape of a cluster is determined by the balance of the forces between the surface and the interfacial energy. Isotropy of clusters varies the mechanism as given in Figure 1 [16].…”
Section: Motivation and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, even more complex catalyst model systems have been prepared. These include metal particles deposited on oxide supports [7][8][9], as well as alkali metal promoted model catalyst films [10][11][12]. The interaction of potassium with well-defined oxide surfaces has been subject to several investigations [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%